(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The catalytic carbonation reaction of methane with carbonic anhydride in the gas phase in the presence of catalysts was carried out in a flow reactor (diameter 2 cm and length 20 cm), at normal atmospheric pressure, a volume flow rate of 1000 h-1 and at 750-1000°C. The catalyst volume was 6 ml, and the catalyst operating time was 240-264 h.